Inpatient HbA1c testing: a prospective observational study. Issue 1 (7th September 2015) - Nanayakkara, Natalie; Nguyen, Hang; Churilov, Leonid; Kong, Alvin; Pang, Nyuk; Hart, Graeme K; Owen-Jones, Elizabeth; White, Jennifer; Ross, Jane; Stevenson, Victoria; Bellomo, Rinaldo; Lam, Que; et al.
Abstract : Objective: To use admission inpatient glycated hemoglobin (HbA1c) testing to help investigate the prevalence of unrecognized diabetes, the cumulative prevalence of unrecognized and known diabetes, and the prevalence of poor glycemic control in both. Moreover, we aimed to determine the 6-month outcomes for these patients. Finally, we aimed to assess the independent association of diabetes with these outcomes. Research, design, and methods: Prospective observational cohort study conducted in a tertiary hospital in Melbourne, Australia. Patients: A cohort of 5082 inpatients ≥54 years admitted between July 2013 and January 2014 underwent HbA1c measurement. A previous diagnosis of diabetes was obtained from the hospital medical record. Patient follow-up was extended to 6 months. Results: The prevalence of diabetes (known and unrecognized) was 34%. In particular, we identified that unrecognized but HbA1c-confirmed diabetes in 271 (5%, 95% CI 4.7% to 6.0%) patients, previously known diabetes in 1452 (29%, 95% CI 27.3% to 29.8%) patients; no diabetes in 3359 (66%, 95% CI 64.8–67.4%) patients. Overall 17% (95% CI 15.3% to 18.9%) of patients with an HbA1c of >6.5% had an HbA1c ≥8.5%. After adjusting for age, gender, Charlson Index score, estimated glomerular filtration rate, and hemoglobin levels, with admission unit treated as a random effect, patients with previously known diabetes had lower 6-month mortality (OR 0.69, 95% CI 0.56 to 0.87, p=0.001). However, there were no significant differences in proportions of intensive care unit admission, mechanical ventilation or readmission within 6 months between the 3 groups. Conclusions: Approximately one-third of all inpatients ≥54 years of age admitted to hospital have diabetes of which about 1 in 6 was previously unrecognized. Moreover, poor glycemic control was common. Proportions of intensive care unit admission, mechanical ventilation, or readmission were similar between the groups. Finally, diabetes was independently associated with lower 6-month mortality.